Baudelaire and Gautier: Some Aspects of a Literary Relationship - Holden, Anita (My University, 2024)
An examination of the affinities between Baudelaire and Gautier in matters of aesthetic principle, as seen in the light of their personal relations, the social climate of their times, and their works.
Keywords: French